The Role of Purchase Intention in Mediating the Influence of Lifestyle Shopping and Visual Merchandising on Impulse Buying: A Study on Lazada Consumers in Denpasar City - Dina Isana Dewi, Brigitta; Trianasari, Trianasari; Suarmanayasa, I Nengah (Jurnal Locus Penelitian dan Pengabdian, 2026)
The phenomenon of impulse buying behavior in Indonesia has increased year by year, with many people exhibiting consumptive behavior. This consumptive behavior is driven by factors such as shopping lifestyle and visual merchandising, which in turn influence purchase intention and impulse buying actions. The purpose of this study is to test and analyze the influence of shopping lifestyle, visual merchandising, and purchase intention on impulse buying among Lazada consumers in Denpasar City. This research examines the effects of shopping lifestyle and visual merchandising on purchase intention and impulse buying, with purchase intention acting as a mediating variable.Using purposive sampling, 96 respondents were selected based on the Cochran formula. Data were analyzed using descriptive statistics and Partial Least Squares (PLS). The results of the analysis show that shopping lifestyle, visual merchandising, and purchase intention have a positive and significant effect on impulse buying among Lazada consumers in Denpasar City. Furthermore, shopping lifestyle and visual merchandising have a positive and significant effect on purchase intention in Lazada consumers in Denpasar City. Purchase intention also positively and significantly mediates the relationship between shopping lifestyle, visual merchandising, and impulse buying among Lazada consumers in Denpasar City